Economic vulnerability of timber resources to forest fires. - Rodríguez y Silva, Francisco; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera; y Silva, Francisco Rodríguez; Molina, Juan Ramón; González-Cabán, Armando; Machuca, Miguel Ángel Herrera (Journal of environmental management, 2012)
The temporal-spatial planning of activities for a territorial fire management program requires knowing the value of forest ecosystems. In this paper we extend to and apply the economic valuation principle to the concept of economic vulnerability and present a methodology for the economic valuation of the forest production ecosystems. The forest vulnerability is analyzed from criteria intrinsically associated to the forest characterization, and to the potential behavior of surface fires. Integrating a mapping process of fire potential and analytical valuation algorithms facilitates the implementation of fire prevention planning. The availability of cartography of economic vulnerability of the forest ecosystems is fundamental for budget optimization, and to help in the decision making process.
Keywords: Conservation of Natural Resources; Conservation of Natural Resources: economics; Decision Making; Economic valuation; Ecosystem; Fire economic losses; Fire prevention planning; Fires; Timber valuation; Trees

Wood provisioning in Mediterranean forests: A bottom-up spatial valuation approach - Ojea, Elena; Ruíz-Benito, PALOMA; Markandya, Anil; Zavala, MIGUEL a (Forest Policy and Economics, 2012)
The science of ecosystem services has evolved signiﬁcantly in the last decade following an increase in interest in the understanding and valuation of these services. Forests provide important ecosystem services that supply societal needs, such as timber, but this provision is not free of conﬂicts derived from the intensive management of forests. A GIS based approach using data from national forest inventories allows us to identify the provision of timber services and to conduct its valuation. The analysis includes a sample of 37,761 plots for 38 commercial tree species in the Spanish Mediterranean region, where we identify sustainable and nonsustainable forests in terms of harvesting intensities and value both the ﬂow of beneﬁts and their net present value. From the analysis we conclude that non-sustainable forests are providing higher economic returns than sustainable forests for most abundant tree species. However, when analysing long term trends, results show that sustainable forests yield higher economic beneﬁts. This latter perspective is preferred when looking at the value of timber as a provisioning service of forests. According to our results, if we wish to encourage sustainability we need to (a) get lower discount rates adopted for the private sector and (b) ensure longer time horizons.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Economic valuation; GIS; mediterranean forest; Non-sustainable harvest; Sustainable harvest; Timber provisioning